Electrochemical Detection of Alzheimer’s Disease Biomarker, β-Secretase Enzyme (BACE1), With One-Step Synthesized Reduced Graphene Oxide - Dey, Jhilik; Roberts, Akanksha; Mahari, Subhasis; Gandhi, Sonu; Tripathi, Prem Prakash (Frontiers in Bioengineering and Biotechnology, 2022)
β-Secretase1 (BACE1) catalyzes the rate-limiting step in the generation of amyloid-β peptides, that is, the principal component involved in the pathology of Alzheimer’s disease (AD). Recent research studies show correlation between blood and cerebrospinal fluid (CSF) levels of BACE1 with the pathophysiology of AD. In this study, we report one-step synthesized reduced graphene oxide (rGO), activated via carbodiimide chemistry, conjugated with BACE1 antibody (Ab), and immobilized on fluorine-doped tin oxide (FTO) electrodes for rapid detection of BACE1 antigen (Ag) for AD diagnosis. The synthesis and fabrication steps were characterized using different types of spectroscopic, X-ray analytic, microscopic, and voltametric techniques. Various parameters including nanomaterial/Ab concentration, response time, pH, temperature, and rate of scan were standardized for maximum current output using the modified electrode. Final validation was performed via detection of BACE1 Ag ranging from 1 fM to 1 µM, with a detection limit of 0.64 fM in buffer samples and 1 fM in spiked serum samples, as well as negligible cross-reactivity with neurofilament Ag in buffer, spiked serum, and spiked artificial CSF. The proposed immunosensor gave a quick result in 30 s, and good repeatability and storage stability for a month, making it a promising candidate for sensitive, specific, and early diagnosis of AD. Thus, the fabricated electrochemical biosensor for BACE-1 detection improves detection performance compared to existing sensors as well as reduces detection time and cost, signifying its potential in early diagnosis of AD in clinical samples.